A study on factors affecting to the effectiveness of training that provided to Majlis Amanah Rakyat Negeri Sembilan / Nur Natasha Abd Gani - Abd Gani, Nur Natasha (2014)
Training program is very important and take serious concern by human resource and top management in every business field from small and midsize business to global organization, including private and government sector. Many employers believe that training program is very important because it may lead to the low absenteeism, enhance the productivity, as well as motivation for the employee job performance. Organizations make a big amount of investment in implementing every session of training program and they hope employees will change and improve their performance after attended the training program. Because of not all training program is effective and successful implement, so that this study was to examine the factors affecting effectiveness and its implication towards job performance. To examine the study a literature review has been done on different aspects of training. The findings of this study suggest many factors which affect training effectiveness such as Work environment (manager support, peer support and technological support), Trainee's characteristic (motivation and attitude), and training environment. The importance of training effectiveness is also discussed in this study.